Efektivitas Aplikasi Kinemaster terhadap Minat Belajar dan Hasil Belajar Matematika - Ahmad, Herlina; Rahayu, Ayu; Syamsuddin, Syamsuddin; Asia, Nur (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2022)
The purpose of this study was to determine the effectiveness of the kinemaster application on students' interest in learning and learning mathematics outcomes. The research sample was students of class VIIA as the experimental class and class VIIB as the control class. The instrument used in this research is a test of mathematics learning outcomes, especially in comparison materials, activity sheets, learning implementation sheets, response questionnaires, and interest in learning mathematics questionnaires. The data analysis technique used descriptive and inferential statistics. From the results of descriptive statistical analysis, the average value of the pre-test in the experimental class was 43.58 and the pre-test result for the control class was 41.17. Meanwhile, the average post-test score in the experimental class was 80.00 and the post-test result for the control class was 73.73. Inferential statistical analysis obtained tcount of 2.67. While ttable is 1.69, which means that tcount > ttable which means H0 is rejected and H1 is accepted. Activity analysis shows that the activities of students are in the active criteria. The implementation analysis obtained that all were carried out and were in very good criteria. The response questionnaire analysis showed that almost all of the students responded positively. Questionnaire analysis of interest in learning mathematics in the experimental class was 85.2% and in the control class was 70.7%. From the results of the analysis, it was concluded that the use of the kinemaster application was effective on learning interest and mathematics learning outcomes for seventh grade students at Mts Pergis Campalagian.